A tradition of Ricardo Palma or how Satan loses lawsuits by ignoring the rules of contract interpretation - Calderón Puertas, Carlos (2021)
The author - drawing on a tradition of Ricardo Palma - examines the contractual link that arose between an old scribe of Lima and Satan. Previously, he explores Palma’s importance in national literature and gathers other traditions that can be used to introduce the reader to the world of law. Then, within a characteristic plane of law in literature, he uses Palma’s text to specifically address the issue of contractual interpretation, linking the agreements arising from the «Don Dimas de la Tijereta» tradition with the Peruvian Civil Code.